Permainan Ular Tangga Edukasi untuk Meningkatkan Kepercayaan Diri Anak Usia Dini - Aprilia, Samhah Taurisa; Siswono, Hendrik; Sugiarto, Muhammad Agus (STAI Auliaurrasyidin Tembilahan, 2024)
Self-confidence is one of the emotional intelligence that needs to be developed in early childhood. This study aims to improve early childhood self-confidence through educational snakes and ladders games at SPS Lemuru 26 Mojosari, Jember. This research is a Classroom Action Research (CAR) with a population of 10 students aged 4-5 years. Data were collected through observation, field notes, and documentation, then analyzed quantitatively and qualitatively. This research involved one cycle consisting of planning, implementation, observation, and reflection stages, with the target of increasing self-confidence at least 76% of children reaching the “very good” category. The results showed that children's belief in their own abilities and positive attitudes were at 85% (very good), a sense of optimism obtained 75% (good), judging objectively obtained 87.5% (very good), responsibility for the actions taken was at 85% (very good), and the ability to think critically obtained 82.5% and was classified in the category (very good). Thus, the educational snakes and ladders game proved effective in increasing the self-confidence of early childhood.